Transgressing boundaries of grievability: Ambiguous emotions at pet cemeteries. (May 2019) - Schuurman, Nora; Redmalm, David
Highlights: The study focuses on grief for non-human animals at pet cemeteries in Scandinavia. At pet cemeteries, the nature–culture and animal–human dichotomies are blurred. Emotions towards non-human animals are recognised and accepted at pet cemeteries.